2022
DOI: 10.21608/jpp.2023.178703.1197
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Among some of Rice Genotypes under Water Shortage

Abstract: The experiment was carried out in strip plot design with three replications to evaluate 14rice genotypes under normal and water deficit in the field and biotechnology lab of Rice research and Training Center at Sakha Agricultural Research Station, Sakha, Kafr EL-Sheikh Egypt, during2021 and 2022summer seasons. Results revealed a wide variation among rice genotypes and their parents for agronomical characteristics and SSR markers. Data showed that days to maturity, plant height, Flag leaf area, number of panicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…However, the reduction in grain yield as affected by water stress conditions may be due to the reduction in dry matter production, number of panicles -1 and number of filled grains panicle -1 . A similar trend was found by Gewaily et al (2019) and Sedeek et al (2022). Rice crop production has significant challenges from salt dangers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the reduction in grain yield as affected by water stress conditions may be due to the reduction in dry matter production, number of panicles -1 and number of filled grains panicle -1 . A similar trend was found by Gewaily et al (2019) and Sedeek et al (2022). Rice crop production has significant challenges from salt dangers.…”
Section: Discussionsupporting
confidence: 86%
“…Giza 183 is suitable to mechanization harvest due to its short stature compared to Sakha 104 and Sakha 102. Sedeek et al (2022) reported that the reduction in plant height may be due to reduction in cell turgor which induces reduction in cell enlargement, and turn into decreases shoots enlargement and plant height. The study of interaction infection resulted that Giza 183 could easily have performed better under continuous flooding, continuous saturation and cyclic irrigation every 5 days and the reduction in grain yield with prolonging irrigation every 10 and 15 days were (9.83, 9.50, 8.47 and 8.50 t/ha) in both seasons of study, respectively (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…About onethird of total cultivated area is exposed to water shortage annually in Egypt Abdallah et al, (2016). Hence, irrigation water is the most limiting factor for expanding rice cultivation area in Egypt Sedeek et al, (2022) and Shehab et al, (2023).…”
Section: Introductionmentioning
confidence: 99%
“…Low water availability is one of the major causes for crop yield reductions affecting the majority of the farmed regions around the world El-Agoury et al, (2023). As water resources for agronomic uses become more limiting, the development of drought-tolerant lines becomes increasingly more important Daher (2018), Sedeek et al, (2022) and Shehab et al, (2023).…”
Section: Introductionmentioning
confidence: 99%